AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT PISANG KEPOK, PISANG MAS DAN PISANG NANGKA MENGGUNAKAN METODE DPPH - Azimatur Rahmi; Nadya Hardi; Linda Hevira (Universitas Wahid Hasyim Semarang, 2021)
Banana is one of the most common crops in Indonesia. Banana peel contains phenolic antioxidant compounds. This study used extraction, DPPH, and spectrophotometry to determine the potential antioxidant activity of three types of banana peels, namely kepok banana peel, trout banana peel, and jackfruit banana peel. Banana peel simplisia powder was extracted by maceration using 96% ethanol as solvent. The resulting banana peel extract was then phytochemical screening for flavonoid compounds, tannins, alkaloids, steroids, and terpenoids. This antioxidant activity test used a qualitative method using TLC and quantitative method with reagent of 0.2 N DPPH by UVVis spectrophotometry. The results showed that the three banana peels tested had antioxidant activity and it is classified as active. The IC50 values for the ethanolic extracts of kepok banana peel, trout banana peel, and jackfruit banana peel were 9,702 ppm, 13,322 ppm and 10,747 ppm respectively. Ascorbic acid as a comparison obtained an IC50 value of 9,613 ppm. From the data obtained, kepok banana peel extract has the highest antioxidant than extract of trout banana peel, and jackfruit banana peel.